Where we are from matters: Assessing the impact of immigrants on firm environmental performance - LEE, Narae (Institutional Knowledge at Singapore Management University, 2022)
This study examines the impact of immigrant populations on firm environmental performance. Leveraging a longitudinal dataset of more than 11,000 manufacturing facilities in the US in which I match the Environmental Protection Agency’s (EPA) facility toxic emissions data with the location’s census immigration data, I document the negative impact of local immigrant populations on a facility’s environmental performance, which strengthens as heterogeneity among immigrant increases. I argue that this is because a more heterogeneous community is less cohesive and hence less capable of organizing effective pressures against pollution. Further, I show that because co-nationality links create unique bonds between the facility and local immigrants, the negative relationship declines as more immigrants originate from the same home country as a facility’s parent firm. These results are robust to the use of an instrumental variable approach and a wide variety of alternative specifications and subsamples. These findings suggest that local community pressures may be limited in driving better environmental outcomes.